Sea Anemone Kunitz Peptide HCIQ2c1: Structure, Modulation of TRPA1 Channel, and Suppression of Nociceptive Reaction In Vivo - Aleksandra N. Kvetkina; Sergey D. Oreshkov; Pavel A. Mironov; Maxim M. Zaigraev; Anna A. Klimovich; Yulia V. Deriavko; Aleksandr S. Menshov; Dmitrii S. Kulbatskii; Yulia A. Logashina; Yaroslav A. Andreev; Anton O. Chugunov; Mikhail P. Kirpichnikov; et al. (Marine Drugs)
TRPA1 is a homotetrameric non-selective calcium-permeable channel. It contributes to chemical and temperature sensitivity, acute pain sensation, and development of inflammation. HCIQ2c1 is a peptide from the sea anemone Heteractis magnifica that inhibits serine proteases. Here, we showed that HCIQ2c1 significantly reduces AITC- and capsaicin-induced pain and inflammation in mice. Electrophysiology recordings in Xenopus oocytes expressing rat TRPA1 channel revealed that HCIQ2c1 binds to open TRPA1 and prevents its transition to closed and inhibitor-insensitive ‘hyperactivated’ states. NMR study of the 15N-labeled recombinant HCIQ2c1 analog described a classical Kunitz-type structure and revealed two dynamic hot-spots (loops responsible for protease binding and regions near the N- and C-termini) that exhibit simultaneous mobility on two timescales (ps–ns and μs–ms). In modelled HCIQ2c1/TRPA1 complex, the peptide interacts simultaneously with one voltage-sensing-like domain and two pore domain fragments from different channel’s subunits, and with lipid molecules. The model explains stabilization of the channel in the open conformation and the restriction of ‘hyperactivation’, which are probably responsible for the observed analgetic activity. HCIQ2c1 is the third peptide ligand of TRPA1 from sea anemones and the first Kunitz-type ligand of this channel. HCIQ2c1 is a prototype of efficient analgesic and anti-inflammatory drugs.